تسهيل المسهّلين: جهد بناء الإمكانيّات للخرّيجين المقيمين بمعهد التّنويريّة الإسلاميّ من خلال مساعدة الزّراعة المائيّة كتقوية الإحتمال للأشخاص المحلّية - Lesmana, Dede Aditia (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
This practical research aims to understand the processes of helping to build capabilities with graduates who will be facilitators in empowering students through hydroponics at the Tanwiriyah Islamic Boarding School. It also aims to realize the influence of graduates on the program’s duration, as well as to the proportionality between that process and the principles of vocation at once. As for the approach used in this research, it is based on the ABCD approach and by using Appreciative Inquiry procedures through four stages (Discovery, Dream, Design, and Dan Destiny) throughout the process. Marketing and how to read the markets. Using Analyze, it chooses the first step as its main priorities. Otherwise, the vision of the founder of Kiai Haji Mohsin Tanwiri is the best major engine for developing other assets. As for the result of this research, it is the special important impact of the graduates, and from which new thoughts emerged for the development of hydroponics and the increase in the new appointment, and they are the ones who are expected to be the facilitators of student empowerment when students return to the Boarding Islamic Schools. As well as for this program to develop their skills after the spread of the Coronavirus.